2005
DOI: 10.1515/bc.2005.097
|View full text |Cite
|
Sign up to set email alerts
|

Improving the levels of essential amino acids and sulfur metabolites in plants

Abstract: Plants represent the major source of food for humans, either directly or indirectly through their use as livestock feeds. Plant foods are not nutritionally balanced because they contain low proportions of a number of essential metabolites, such as vitamins and amino acids, which humans and a significant proportion of their livestock cannot produce on their own. Among the essential amino acids needed in human diets, Lys, Met, Thr and Trp are considered as the most important because they are present in only low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 134 publications
(190 reference statements)
0
61
0
1
Order By: Relevance
“…The synthesis of aspartate family amino acids is regulated at several junctures (Hesse et al, 2004). Recent efforts have identified a couple of enzymes with the potential to act as suitable regulators (Galili et al, 2005). Several lines of evidence show that the branch point between CgS and TS plays a major regulatory role in the flux of carbon into met.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of aspartate family amino acids is regulated at several junctures (Hesse et al, 2004). Recent efforts have identified a couple of enzymes with the potential to act as suitable regulators (Galili et al, 2005). Several lines of evidence show that the branch point between CgS and TS plays a major regulatory role in the flux of carbon into met.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that elevated levels of the carbon backbone (e.g. over-expression of aspartate kinase) increase the synthesis of lys and thr (Galili, 1995;Galili et al, 2005). This suggests that carbon flux limits the synthesis of met, which itself implies that met levels could be increased if OPHS were available in sufficient amounts.…”
Section: Introductionmentioning
confidence: 99%
“…Information on how to increase the pool of essential amino acids, such as lysine and threonine, as well as on targeting pharmaceutical proteins to specific subcellular compartments, could be used to increase the amount of silk protein produced in plants (Conrad and Fiedler, 1998;Galili et al, 2005). In addition to strategies to optimize expression, a remaining challenge is that effective synthesis of a fibrous protein does not ensure production of a good fiber.…”
Section: Fibrous Proteinsmentioning
confidence: 99%
“…As global population increases steadily and the production of staple plants predicted to escalate considerably, SO 4 2-deficient disorders are expected to become more pregnant along the coming years [155] with significant harmful impact for mankind. Nevertheless, effective preventive efforts are developed in some countries aiming at fortification of soils mainly by ammonium sulfate or calcium sulfate (gypsum) salts, resulting in meaningful improvements in crop yield, SAAs content and biological value and opening more optimistic perspectives for livestock and human consumption [152,[155][156][157][158].…”
Section: The Additional Burden Of S-deficiencymentioning
confidence: 99%